2017
DOI: 10.1039/c7mb00203c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ageing and single nucleotide polymorphisms associated with the risk of aggressive prostate cancer in a New Zealand population

Abstract: Prostate cancer is one of the most significant male health concerns worldwide, and various researchers carrying out molecular diagnostics have indicated that genetic interactions with biological and behavioral factors play an important role in the overall risk and prognosis of this disease. Single nucleotide polymorphisms are increasingly becoming strong biomarker candidates to identify the susceptibility of individuals to prostate cancer. We carried out risk association of different stages of prostate cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Single nucleotide polymorphisms (SNPs), a common type of genetic variation, present in lncRNAs have been found to be able to affect the structure, expression level, and function of lncRNAs by interfering with the corresponding target mRNAs [7]. Evidence has demonstrated that SNPs in lncRNA genes were related to the occurrence of various diseases, particularly cancer [8]. Therefore, lncRNA polymorphisms are considered to be potentially associated with the mechanism underlying cancer susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs), a common type of genetic variation, present in lncRNAs have been found to be able to affect the structure, expression level, and function of lncRNAs by interfering with the corresponding target mRNAs [7]. Evidence has demonstrated that SNPs in lncRNA genes were related to the occurrence of various diseases, particularly cancer [8]. Therefore, lncRNA polymorphisms are considered to be potentially associated with the mechanism underlying cancer susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand (NZ) there were 3199 PC registrations and 607 PC-related deaths in 2012[3]. The status of PC risk varies between individuals in terms of the patient’s lifestyle and biological characteristics [46]. For PC management purposes, it is important to differentiate between men carrying indolent cancers from those with high-risk cancers.…”
Section: Introductionmentioning
confidence: 99%